Feeding habits and habitat use in Bothrops pubescens (Viperidae, Crotalinae) from southern Brazil - Hartmann, Marília T.; Hartmann, Paulo A.; Cechin, Sonia Z. [UNESP]; Martins, Marcio (Society for the Study of Amphibians and Reptiles, 2005)
Bothrops pubescens is a member of the neuwiedi complex that occurs in southern Brazil and Uruguay. We studied the ecology of B. pubescens from a field site (at Santa Maria, Rio Grande do Sul, Brasil) and based on preserved specimens from the state of Rio Grande do Sul, Brasil. In Santa Maria, individuals were collected during visual encounter surveys (VES), in pitfall traps with drift fences and during incidental encounters. Most snakes found in the field were on the ground, mainly on leaf litter, in mosaics of light and shadow or in completely shaded areas. In disturbed areas, snakes were usually associated with country houses and agricultural fields. Snakes were found much more frequently in forests and forest edges than in open habitats. The diet of B. pubescens comprised small mammals (56.2% of individual prey found), anurans (21.2%), lizards (7.5%), snakes (7.5%), birds (5.0%), and centipedes (2.5%). Prey predator mass ratios ranged from 0.002-0.627, and larger snakes tended to consume larger prey. Bothrops pubescens seems to be able to survive in disturbed areas, mainly those close to forests, and this ability may be facilitated by its generalized feeding habits. Copyright 2005 Society for the Study of Amphibians and Reptiles.
Keywords: Anura; Aves; Bothrops; Chilopoda; Crotalinae; Mammalia; Serpentes; Squamata; Viperidae